'Be a Warrior, not a Worrier…': The Resilience of Vice Principals at Turkish Schools - Ceven, Gozde; Er, Emre; Ongel, Gulay (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
Resilience in education has drawn scholarly attention over the past two decades because of its potential to strengthen the adaptative skills of students, teachers, and school principals and foster the sustainability of the school environment in the face of adverse conditions in today's world uncertainty. However, as a crucial staff in adapting and developing in challenging times, school vice principal resilience has been neglected. This study aims to gain an in-depth understanding of vice principals' experiences concerning their resilience based on the risk factors, and protective factors.The study is qualitative research, incorporating phenomenology design. Thematic analysis was used to investigate vice principals' experiences pertaining the resilience. The analysis drew on data collected from semi-structured interviews carried out with 10 vice principals at Turkish schools. Overall, the findings reveal that risk factors are bureaucratic climate, lack of professionalism, and financial problems; protective factors are individual factors, social factors, and environmental factors; positive outcomes are being a more patient person, having a broader perspective, larger social network, and a larger influence area. This study offers insight into the need to conduct longitudinal research to fully understand vice principals' resilience.
Keywords: RISK; Education & Educational Research